Strength Analysis of Seaweed Cultivation Module - Ketkale, Sourabh Sukumar; Rimovskis, Sergėjus (Jaunųjų mokslininkų darbai, 2018)
This paper is an attempt to a new approach in seaweed cultivation module that is carried out by a company UAB Metal Production in Lithuania. The article is concerned with how the module made of PE80 works under given conditions. The aim was to study the design of seaweed cultivation module, determine its stresses and displacements with Solidworks Simulation. The maximum depth of immersion up to 30 m is considered, as well as influence of seawater flow. It was determined that the module is designed within the factor of safety limits.
Keywords: Seaweed cultivation module; FEM; PE80 strength